Ethanol Increases Endothelial Nitric Oxide Production through Modulation of Nitric Oxide Synthase Expression - Venkov, Christo D.; Myers, Paul R.; Tanner, Miles A.; Su, Ming; Vaughan, Douglas E. (Thrombosis and Haemostasis, 1999)
Moderate alcohol consumption has been shown to reduce the risk of ischemic heart disease potentially through its effect on specific endothelial-derived compounds. We tested the hypothesis that ethanol increases the expression of endothelial nitric oxide synthase (eNOS) and nitric oxide (NO) production in bovine aortic endothelial cells (BAEC). Primary cultures of BAEC grown to confluence under standard conditions were treated 3-6 h with 0.1% ethanol in the presence of indomethacin. Ethanol induced a significant increase in both basal and stimulated NO production as determined by chemiluminescence method. This effect was accompanied by a rapid increase of eNOS protein and mRNA expression levels. eNOS mRNA increased two-fold within 3 h and gradually declined, but the increased levels of mRNA persisted for >24 h. A similar increase of eNOS expression was observed in human umbilical endothelial cells exposed to ethanol. These results demonstrate that ethanol augments both basal and stimulated NO production and that this effect is associated with increased eNOS protein and mRNA expression levels. The data are consistent with the hypothesis that the reduced incidence of ischemic heart disease associated with alcohol may be related, at least in part, to the modulation of vascular endothelial cell production of NO